The Changing of economics that effected to social status of community in Chiang Mai province - ชำนาญ ตระกูล (Community and Social Development Journal, 2018)
ABSTRACT The research objectives were 1) to study the changing of economics that effected to social status of community. 2) to study the relationship between personal factors and the changing of economics and society of people in community. 3) to find out the suggestions for the people on how to live in community under condition of changing of economics and current society. The research found out as the followings: 1) mostly informants are male 72.2 percent and 27.8 percent is female. The age of informants during 18-30 years old is 41.1 percent, the age of informants during 41-50 years old is 32.4 percent, the age of informants during 31 – 40 years old is 19.1 percent and the people above 50 years old is 7.5 percent, the mostly informants are Buddhist 79.3 percent and Christian 20.72. 2) Sex and the changing of society and economics of community related to hypothesis by the statistical significance level of 0.05 and the relationship between social economics factors and the impact of way of life of the people in community related to hypothesis by significance level of 0.05. 3) the suggestions are to support the people to preserve old custom, culture and to protect the people from drugs. Key words: Changing of social economics, social impact